2019
DOI: 10.1111/adb.12753
|View full text |Cite
|
Sign up to set email alerts
|

Chronic calorie‐dense diet drives differences in motivated food seeking between obesity‐prone and resistant mice

Abstract: Obesity results from overconsumption of energy, partly because of the inability to refrain from highly palatable rewarding foods. Even though palatable food is available to everyone, only a fraction of the population develops obesity. We previously showed that following chronic exposure to highly palatable food animals that gained the most weight also showed addictive-like motivation to seek for palatable food. An important question remains-is this extreme, addictive-like, motivation to consume palatable food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 40 publications
(61 reference statements)
4
17
0
Order By: Relevance
“…Note that there was no correlation between the head entries and the lever presses ( Figure 5C), confirming our previous finding that prior to the chronic consumption of HFHS diet head entries may be a better predictor of future weight gain than operant food seeking (20).…”
Section: Obesity-prone Mice Show Decreased Excitability In the Vp Comsupporting
confidence: 88%
See 4 more Smart Citations
“…Note that there was no correlation between the head entries and the lever presses ( Figure 5C), confirming our previous finding that prior to the chronic consumption of HFHS diet head entries may be a better predictor of future weight gain than operant food seeking (20).…”
Section: Obesity-prone Mice Show Decreased Excitability In the Vp Comsupporting
confidence: 88%
“…Lastly, we were able to identify the tendency to show long term potentiation in the VP as a possible innate marker for excessive gain of weight when chronically 9 exposed to HFHS diet. In a previous study we showed that OP mice seek for palatable food more intensely (higher head entries to the food receptacle) than OR mice even before being exposed to chronic HFHS diet (20). Thus, we used here the intensity of food seeking in HFHSnaive mice as a possible marker for future weight gain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations